Knowledge and performance in innovative firms: An analysis of district and inter-district effects - Manuel Lopez-Estornell; Ignacio Fernández de Lucio (European Regional Science Association (ERSA), 2011)
The first aim of the paper is to analyze the presence of knowledge in innovative firms located in industrial districts (ID) in order to contrast it with this kind of firm located in non industrial districts areas (NID). This approach assumes the presence of an industrial district effect, i.e., the presumption of a better performance of knowledge and economic results in the first group of firms. Second, we have attempted to identify the existence of interdistrict effect, i.e., the emergence of gaps in knowledge of innovative firms located in ID with different technological intensity. For both purposes we have chosen the Valencian ID in Spain. Besides, with the introduction of innovative firms as units of analysis we have assumed that: a) They reflect a superior use of knowledge resources as inputs for business innovation generation and b) Their greatest use of such resources facilitate the absorption of knowledge spillovers that flow through the district. The empirical analysis has used an unprecedented database containing information of 5,553 innovative companies we have found in the region. The mean analysis applied has allowed us to identify the variables with statistically significant differences, as a preliminary step to isolate the groups of firms with more pronounced central values. The results have shown the presence of differences characterizing differently innovative companies of ID and NID as well as the groups of innovative firms belonging to districts of different technological level. In the first case the superiority of innovative companies has not arisen and, consequently, we cannot confirm the existence of a district effect. Nevertheless, we have detected some evidence of inter-industrial effect in the gradation performance of innovation firms of shoes, textiles and tales.
Keywords: 330